Under the Empire of Spontaneous Solidarity: State and Political Action in the Theoretical Durkheimian Project (1892-1893) - Inda, Graciela (2019)
This paper aims at identifying and examining all the principles arisen from the issues of the state and politics in Durkheim’s production during the period 1892-1893, signaled by the publication of his famous thesis on the cohesive role of the division of social labor. According to the in-depth analysis carried out in this article, the most important points of Durheim’s politics are four. Firstly, the conception of the state as an organ that translates an automatic social solidarity because it is an entire entity preexisting any political relationships. Secondly, the distinction of despotism as a regime that implies the complete absorption of individuals by the political apparatus. Thirdly, the problem of the growing enlargement of the state interventions in the individuals’ private life sphere. Finally, the incapacity of any political action to transform the society’s morphology.